Analisis Dampak Sosial Media Terhadap Keriligiusan Peserta Didik (Studi Literatur) - Oktavia, Lidya Fransiska; Refnawati, Refnawati; Yovica, Alia; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2024)
The digital era marked by technological advancements and the popularity of social media has reshaped the values, beliefs, and spiritual practices held by young people. For students, social media is a complex world. This platform can be a source of spiritual inspiration, but it can also divert their attention to worldly things that are not in accordance with religious values. Therefore, this study aims to analyze existing research on the relationship between social media and student religiosity. The research method used is a literature study. There are several studies related to social media and its impact on student religiosity. The search strategy is carried out systematically by reviewing articles that have been published on Google Scholar. Based on the results of a systematic review of the literature, it was found that there was an impact of social media on the level of religiosity of students because students were negligent in the implementation of religious values in school and they also forgot the religious norms assigned or required to them